The National Toxicology Program Web-based Nonneoplastic Lesion Atlas: A Global Toxicology and Pathology Resource - Cesta, Mark F. (Toxicol Pathol, 2014)
Toxicologists and pathologists worldwide will benefit from a new, website-based and completely searchable Nonneoplastic Lesion Atlas just released by the U.S. National Toxicology Program (NTP). The Atlas is a much-needed resource with thousands of high quality, zoomable images and diagnostic guidelines for each rodent lesion. Liver, gall bladder, nervous system, bone marrow, lower urinary tract and skin lesion images and diagnostic strategies are available now. More organ and biological systems will be added with a total of 22 chapters planned for the completed project. The Atlas will be used by the NTP and its many pathology partners to standardize lesion diagnosis, terminology and the way lesions are recorded. The goal is to improve our understanding of nonneoplastic lesions, and the consistency and accuracy of their diagnosis between pathologists and laboratories. The Atlas is also a useful training tool for pathology residents and can be used to bolster any organization’s own lesion databases. Researchers have free access to this on-line resource at www.ntp.niehs.nih.gov/nonneoplastic.